Technology and Integral Ecology. (24th February 2022) - Russell, Cathriona
Abstract: This paper begins with two preliminary forays, the first into creation theology and its deployment in environmental ethics, and the second sketches some implications for 'integral ecology' of reading theological ethics through the lens of human freedom and autonomy. The third and main focus of the paper is an exploration of aspects of the philosophy of technology, thinking in terms of the 'technocratic paradigm' and human 'agency in context'. This analysis points to the potential for reimaging technologies for a sustainable planet and presents two examples: one new, the management of drone technologies and bird habitat; and one old, rethinking city transport though reinterpreting cycling as development at all income levels. This article is also intended as a contribution to the ongoing development of the concept of 'integral ecology' and its application: a concept that has now been added to related key principles of the common good in the Catholic social tradition: solidarity, subsidiarity, participation.